An Empirical Investigation of the Exchange Rate Pass-Through to Inflation in Tanzania - Mwase, Nkunde (Washington, D.C. : International Monetary Fund, 2006)
The paper examines the effect of exchange rate changes on consumer prices in Tanzania using structural vector autoregression (VAR) models. Using a data set covering the period 1990-2005, we find that the exchange rate pass-through to inflation declined in the late 1990s despite the depreciation of the currency. This could be partly attributed to the macroeconomic and structural reforms that were implemented during this period. The decline in the pass-through does not necessarily imply that exchange rate fluctuations are less significant in explaining macroeconomic fluctuations. The recent increase in the share of imports in the economy suggests that the pass-through could rise over the medium term. The findings imply that the authorities should remain vigilant in assessing the potential impact of foreign prices on the dynamics of inflation in Tanzania. In this regard, the authorities should seek to maintain low and stable inflation and continue the ongoing structural reforms designed to improve efficiency and increase competition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet